2006
DOI: 10.1540/jsmr.42.103
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker activity in the upper urinary tract

Abstract: Ureteral peristaltic activity begins with the origin of electrical activity at pacemaker sites. These sites are located in the proximal portion of the urinary collecting system. The 'atypical' smooth muscle cells at these sites fire 'pacemaker' potentials at a frequency higher than the 'driven' action potentials recorded from typical smooth muscle cells. In contrast to typical smooth muscle cells, these atypical pacemaker cells have less than 40% of their cellular area occupied by contractile filaments and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 49 publications
2
22
0
2
Order By: Relevance
“…In the UUT, it is well established that a tonic production of prostaglandins is critical in the maintenance of UUT contractility (Lang et al, 2002;Weiss et al, 2006). Indeed, we have previously demonstrated that Cox-1 is the primary enzyme involved in synthesizing these prostaglandins in the rat UUT, while Cox-2 is the active enzyme in the guinea pig UUT.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the UUT, it is well established that a tonic production of prostaglandins is critical in the maintenance of UUT contractility (Lang et al, 2002;Weiss et al, 2006). Indeed, we have previously demonstrated that Cox-1 is the primary enzyme involved in synthesizing these prostaglandins in the rat UUT, while Cox-2 is the active enzyme in the guinea pig UUT.…”
Section: Discussionmentioning
confidence: 80%
“…The length and velocity of movement of a bolus of urine in strepozotocin (STZ)-induced diabetic rats is significantly decreased when compared with control or sucrose-diuretetic rats (Watanabe and Miyagawa, 2002). Although the spontaneous contractions in the upper urinary tract (UUT) of many mammalian species are thought to myogenic in origin, capsaicin desensitization or inhibition of prostaglandin synthesis profoundly affect pelviureteric peristalsis, changing either the amplitude and/or frequency of contractions in a species dependent manner (Davidson and Lang, 2000;Lang et al, 2002;Weiss et al, 2006). The aim of this study was to further investigate the effects of DM on pelvureteric peristalsis.…”
Section: Introductionmentioning
confidence: 99%
“…Если к особенностям электрической спонтанной активности данного органа можно отнести строгую ритмичность [4,5], то в мышечных слоях стенок мочевого пузыря регистрируются сопряженные со спайковой пейсмекерной активностью нераспространяющиеся микроконтрактуры. При этом возможно также объединение отдельных потенциалов в группы в виде вспышек активности, которе ассоциируются с последующей контрактурой [6,7,8].…”
Section: удк 61273+612468unclassified
“…Условия для продвижения мочи вдоль мочеточников создаются при возникновении спонтанной контрактуры, сопряженной с пейсмекерной электрической активностью. Пейсмекерный ритмогенез возникает в проксимольной зоне почечной лоханки и впоследствии, координируясь, распространяетcя вдоль мочеточника [2,3].Если к особенностям электрической спонтанной активности данного органа можно отнести строгую ритмичность [4,5], то в мышечных слоях стенок мочевого пузыря регистрируются сопряженные со спайковой пейсмекерной активностью нераспространяющиеся микроконтрактуры. При этом возможно также объединение отдельных потенциалов в группы в виде вспышек активности, которе ассоциируются с…”
unclassified
“…The rhythmic contractions of ureter are driven by propagating membrane depolarization. Myogenic and neurogenic nature of muscle contraction is still discussed on the basis of calcium and Rho-kinase cellular contractility mechanisms and peculiarities of UUT innervation (Kobayashi 1965;Notley, 1971;Santicioli & Maggi, 1998;Levent & Buyukafsar, 2004;Weiss et al, 2006;Hurtado, et al, 2010;Grisk, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%